2016 International Conference for Students on Applied Engineering (ISCAE) 2016
DOI: 10.1109/icsae.2016.7810191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vehicle platooning aerodynamics using bluff body wake generators and CFD

Abstract: Recent developmentsin sensing and communications between vehicles (V2V) and their surroundings have provided the technology to allow cars to operate autonomously or semi-autonomously in closely spaced 'platoon' formation without the risk of collision. This is known to reduce the aerodynamic drag and thus consequently limits the energy consumption and associated emissions. Although wind tunnel investigations have been performed to mimic platoon operations, most experimental evaluations of multiple vehicles in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The adopted CFD settings were previously validated and proven to correlate with experimental measurements of vehicles in platoon. 4,5 The platoon configurations including the inter-vehicle spacing and Reynolds number were identical for the CFD and track measurements to allow for a direct comparison, although, the vehicle geometry was simplified in CFD by enclosing the front grill, wheelhouse, wheels and smoothing the underbody. Enclosure of the front grill is known to reduce the drag of the vehicle as the internal flows are neglected.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The adopted CFD settings were previously validated and proven to correlate with experimental measurements of vehicles in platoon. 4,5 The platoon configurations including the inter-vehicle spacing and Reynolds number were identical for the CFD and track measurements to allow for a direct comparison, although, the vehicle geometry was simplified in CFD by enclosing the front grill, wheelhouse, wheels and smoothing the underbody. Enclosure of the front grill is known to reduce the drag of the vehicle as the internal flows are neglected.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of both parameters increase as the inter-vehicle spacing is reduced and therefore to capture the time-dependent flow dynamics accurately the use of unsteady simulation approaches is vital. However, for drag estimations and general surface pressure trends, 4,5 showed that the Reynolds Averaged Navier-Stokes (RANS) is capable of producing reasonable results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both He et al and Bruneau, Khadra, and Mortazavi demonstrated the advantages of using higher order numerical solvers to determine time dependant flow features in platoon that are usually omitted by RANS that contribute to the vehicle's lateral instability. However, in terms of the averaged flow features that influence the mean drag measurements, the RANS solver has been shown to reproduce the wake structures and pressure field reasonably well for various aerodynamic studies including Bordei and Popescu (2011), Axerio et al (2009), Soares, Garry, and Holt (2017), Fu et al (2017), Maleki, Burton, and Thompson (2017) and Ebrahim, Dominy, and Leung (2016).…”
Section: Introductionmentioning
confidence: 96%